Describe the location of the point having the following coordinates.
abscissa and ordinate have the same sign

the first and the third quadrants have the same sign.

Expert answered|trena99|Points 203|

Expert answered|trena99|Points 203|

Expert answered|trena99|Points 203|

Question

Asked 6/8/2011 12:10:37 PM

0 Answers/Comments

Rating

There are no new answers.

Which of the following would eliminate the variable on the left side of the given equation?
36 - 19w = -6w + 41 **Weegy:** are there any possible answers? **User:** possible answers add -19w
add 6w
add 19w
add -36 **Weegy:** 3. 19w **User:** what does the 3 mean? **Weegy:** the possible answer number 3 **User:** ok! thanks **Weegy:** I'm glad i helped. **User:** i have more questions hold on please. (More)

Question

Expert Answered

Updated 9/19/2014 2:15:52 AM

0 Answers/Comments

What is the solution set of the given equation?
4y - 6y + 9y = -2 **Weegy:** y = -2/7 (More)

Question

Expert Answered

Updated 6/26/2014 9:33:21 PM

2 Answers/Comments

Solve for A.
BA + C = D User: no that is incorrect. User: here is the problem. Solve for A.
BA + C = D . . .here are the possible answers:A = D - B - C
A = (D - C)/B
A = (C - D)/B

Question

Expert Answered

Updated 10/17/2011 8:16:42 PM

2 Answers/Comments

Anonymous

kjlkj

Added 10/17/2011 8:14:44 PM

Anonymous

A=(D-C)/B

Added 10/17/2011 8:16:42 PM

Which of the following is the solution set of the given equation?
(x - 3) - 2(x + 6) = -5 **Weegy:** possible answers? **User:** possible answers are:{-10}
{-4}
{8} **Weegy:** its -10. wait ill check again **User:** ok thanks **Weegy:** do you have any other questions? **User:** yes hold on please (More)

Question

Expert Answered

Updated 7/31/2014 2:40:15 PM

1 Answer/Comment

(x - 3) - 2(x + 6) = -5;

x - 3 - 2x - 12 = -5;

-x - 15 = -5;

-x = -5 + 15;

-x = 10;

x = -10

x - 3 - 2x - 12 = -5;

-x - 15 = -5;

-x = -5 + 15;

-x = 10;

x = -10

Added 7/31/2014 2:40:15 PM

This answer has been confirmed as correct, not copied, and helpful.

Solve for B.
A = 3(B + C) **Weegy:** a=3b+3c b=(3c-a)/3 c=(3b-a)/3 (More)

Question

Updated 6/1/2014 5:50:44 PM

1 Answer/Comment

A = 3(B + C)

A = 3B + 3C

A - 3C = 3B

B = 1/3(A - 3C)

A = 3B + 3C

A - 3C = 3B

B = 1/3(A - 3C)

Added 6/1/2014 5:50:44 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by andrewpallarca [6/2/2014 11:33:57 AM]

23,031,367 questions answered

There are no comments.